The Effects of the Intensity, Timing, and Persistence of Personal History of Mobility on Support for Redistribution - Dabalen, Andrew; Parinduri, Rasyad; Paul, Saumik (World Bank, Washington, DC, 2014)
This paper examines the association between the intensity, timing, and persistence of personal history of mobility on individual support for redistribution. Using both rounds of the Life in Transition Survey, the paper builds measures of downward mobility for about 57,000 individuals from 27 countries in Eastern Europe and Central Asia. The analysis finds that more intensive, recent, and persistent downward mobility increases support for redistribution more. A number of extensions and checks are done by, among others, taking into account systematic bias in perceived mobility experience, considering an alternative definition of redistributive preferences, and exploring the severity of omitted variable bias problems. Overall, the results are robust.